Fangirl - ROWELL, Rainbow. (St. Martin's Griffin, 2013)
Being consummate fans of the Simon Snow series helped Cath and her twin sister, Wren, cope as little girls whose mother left them, but now, as they start college but not as roommates, Cath fears she is unready to live without Wren holding her hand--and without her passion for Snow.